Biceps-related complications after tenotomy associated with arthroscopic rotator cuff repair: risk factors and clinical impact. Issue 3 (30th March 2022) - Ranieri, Riccardo; Nabergoj, Marko; Le Coz, Pierre; Lädermann, Alexandre; Collin, Philippe
Objectives: Many studies have investigated the differences between tenotomy and tenodesis, while only a few have specifically examined the results of tenotomy associated with rotator cuff repair (RCR). Our aim is to report the rate of biceps-related complications after long head of biceps (LHB) tenotomy associated with RCR. Methods: A single-center prospective observational study was conducted between 2015 and 2017 on consecutive patients who underwent RCR associated with LHB tenotomy. Patients were clinically evaluated preoperatively, at 6 months (also by ultrasound) and 1 year, and screened for postoperative Popeye deformity, cramps and bicipital discomfort. Each complication was analyzed for the following risk factors: age, gender, BMI, dominant arm, manual work, type of tear, tendon healing. Finally, clinical outcome was compared between patients with at least one complication and those with none. Results: 207 patients were analyzed. Cramps, Popeye deformity, and discomfort, were, respectively, present in 16 (7.7%), 38 (18.4%) and 52 (25.1%) cases at 6 months and 17 (8.2%), 18 (8.7%) and 24 (11.6%) cases at 1 year. Cramps were associated with lower age (1 year-increase OR = 0.88-95% CI, 0.81-0.96-), higher BMI (1 point-increase OR = 1.1-95% CI, 1.02 -1.23-), single tendon tear (P = 0.0168), manual work (OR = 5.0-95% CI, 1.5-16.0-) at 6 months and manual work (OR = 2.9-95% CI, 1.1-8.3-) at 1 year. Objective Popeye deformity was associated with male gender at 6 months (OR = 6.9-95% CI, 3.0-15.5-). Discomfort was associated with lower age (OR = 0.94-95% CI, 0.90-0.98-), manual work (OR = 2.3 -95% CI, 1.2-4.3-), Popeye deformity (OR = 2.3-95% CI, 1.1-4.9-) at 6 months and manual work (OR = 2.8-95% CI, 1.1-6.6-), single tendon tear (OR = 4.9 -95% CI, 1.1-21.3-) and Popeye deformity (OR = 3.4 -95% CI, 1.1-10.7-) at 1 year. Patients without complications showed a significantly higher Constant, pain and SSV score (75.4 vs 70.4, P = .00252; 0.9 vs 1.9, P <0.00001; 80.2 vs 76.4; P =.00124) at 6 months, and pain and SSV score (0.6 vs 2.0; P = 0.00044; 91.1 vs 77.8; P = <0.00001) at 1 year. Conclusion: Younger age, higher BMI, manual work and single tendon tears are risk factors associated with biceps-related symptoms during the first year. Popeye deformity occurs more frequently in males and is associated with discomfort. Nevertheless, the short-term clinical influence of biceps complications on shoulder outcome is very limited.